Photovoltaic System with INC MPPT Algorithm in MATLAB Simulink - F.Z. Hamidon (2013)
Recent changes within the electricity industry, such as the 2% new renewable energy targets and green energy marketing schemes specifically in Malaysia will see significant growth in the number of photovoltaic (PV) generating systems connected to the grid. PV system that uses the photovoltaic array as a source of electrical power supply has an optimum operating point, called the maximum power point (MPP) which varies mainly depending on cell temperature and the irradiance level. Thus, a maximum power point tracking (MPPT) scheme is needed to operate the PV array at its maximum power point. The MPPT works by automatically tracking the MPP of the PV array so that the overall PV system would have highest performance in terms of the power generated from the PV array will be optimally consumed.This paper presents the model-based design simulation analysis of grid-connected photovoltaic system with Incremental Conductance (INC) MPPT algorithms. The simulation works are carried out in MATLAB Simulink. The performance analysis with regards to the MPPT convergence speed and efficiency are evaluated with respect to rapid change of of irradiance level under local conditions. Simulation results show that the MPPT with INC algorithm offers the best performance in terms of its fastest response in tracking new MPP and highest efficiency under rapid change of irradiance level.